CEACAM1-4L Promotes Anchorage-Independent Growth in Melanoma - Löffek, Stefanie; Ullrich, Nico; Görgens, André; Murke, Florian; Eilebrecht, Mara; Menne, Christopher; Giebel, Bernd; Schadendorf, Dirk; Singer, Bernhard B.; Helfrich, Iris (Frontiers in Oncology, 2015)
Widespread metastasis is the leading course of death in many types of cancer, including malignant melanoma. The process of metastasis can be divided into a number of complex cell biological events, collectively termed the “invasion-metastasis cascade”. Previous reports have characterized the capability of anchorage-independent growth of cancer cells in vitro as a key characteristic of highly aggressive tumor cells, particularly with respect to metastatic potential. Biological heterogeneity as well as drastic alterations in cell adhesion of disseminated cancer cells support escape mechanisms for metastases to overcome conventional therapies. Here we show that exclusively the carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) splice variant CEACAM1-4L supports an anchorage-independent signature in malignant melanoma. These results highlight important variant-specific modulatory functions of CEACAM1 for metastatic spread in patients suffering malignant melanoma.